2020
DOI: 10.1017/s1368980020001020
|View full text |Cite
|
Sign up to set email alerts
|

Equity implications of rice fortification: a modelling study from Nepal

Abstract: Abstract Objective: To model the potential impact and equity impact of fortifying rice on nutritional adequacy of different subpopulations in Nepal. Design: Using 24-h dietary recall data and a household consumption survey, we estimated: rice intakes; probability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Only 42% of women took the recommended dose of 180 IFA tablets, and 69% took deworming tablets during their pregnancy (Ministry of Health Nepal et al, 2017 ), indicating the need to improve these practices in order to improve anaemia. Women's consumption of iron‐rich foods is particularly low in the plains (Harris‐Fry et al, 2018 ), but iron adequacy in women's diets is low across Nepal (Saville, Maharjan, et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only 42% of women took the recommended dose of 180 IFA tablets, and 69% took deworming tablets during their pregnancy (Ministry of Health Nepal et al, 2017 ), indicating the need to improve these practices in order to improve anaemia. Women's consumption of iron‐rich foods is particularly low in the plains (Harris‐Fry et al, 2018 ), but iron adequacy in women's diets is low across Nepal (Saville, Maharjan, et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Nepal et al, 2017), indicating the need to improve these practices in order to improve anaemia. Women's consumption of iron-rich foods is particularly low in the plains (Harris-Fry et al, 2018), but iron adequacy in women's diets is low across Nepal (Saville, Maharjan, et al, 2020).…”
Section: Gender In Nepalmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that administration of iron supplementation, de-worming, and morbidity profile of children do not have significant impact on the prevalence of anaemia. Saville et al (2020) interviewed 4,360 participants including pregnant women, mothers-in-law, and male household heads in Nepal who were consuming fortified rice. Fortification of purchased rice in rice-purchasing households increased (p > .9) for thiamine, niacin, pyridoxin, folate, and zinc, but Vitamin B 12 and iron remained inadequate even after fortification (p > .3-.9).…”
Section: Impact Of Supplementation Of Fortified Rice In Pds As Pilot ...mentioning
confidence: 99%
“…Women's mobility is strictly controlled after marriage and movement outside the household without permission is a common justification for intimate partner violence (36) . Restrictive gender norms limit women's share of the household's food (8,13) , and inadequate consumption of iron-rich foods and other micronutrients essential for healthy erythropoiesis and iron absorption have been reported amongst women in the terai (37)(38)(39) . This research was conducted in two terai provinces: Kapilvastu (Province 5), and Dhanusha and Mahottari (Province 2).…”
Section: Settingmentioning
confidence: 99%